Implementation Of Sharia Marketing In Culinary Business - Hendri Hermawan Adi Nugraha; Nofi Rismawati (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2021)
The purpose of this research is to find out the marketing strategy for the culinary business in Waroeng Qita Pekalongan, to find out the marketing strategy for the culinary business in Waroeng Qita Pekalongan according to the perspective of sharia Marketing and to find out the variables that support and hinder the culinary business marketing development strategy in Waroeng Qita Pekalongan. Sources of data used in this study are primary data sources, secondary data sources, and purposive samples. Primary data sources are interviews with traders and buyers in Waroeng qita kedungwuni Pekalongan and secondary data sources are obtained from the document archives of culinary business managers. In collecting data the researchers used the methods of observation, interviews, and documentation. The results of this study for culinary entrepreneurs in Kedungwuni, Pekalongan Regency are expected to adhere to the values or rules set by Islamic law and must always adhere to Islamic business ethics under any circumstances. It is recommended that all culinary entrepreneurs, especially in Kedungwuni, Pekalongan Regency, try to apply Islamic business ethics as exemplified by the Prophet Muhammad. And it is better for culinary entrepreneurs in Kedungwuni, Pekalongan Regency not only to prioritize world profits but also to prioritize final profits.